Highly active rubiscos discovered by systematic interrogation of natural sequence diversity. (5th June 2020) - Davidi, Dan; Shamshoum, Melina; Guo, Zhijun; Bar‐On, Yinon M; Prywes, Noam; Oz, Aia; Jablonska, Jagoda; Flamholz, Avi; Wernick, David G; Antonovsky, Niv; de Pins, Benoit; Shachar, Lior; et al.
Abstract: CO2 is converted into biomass almost solely by the enzyme rubisco. The poor carboxylation properties of plant rubiscos have led to efforts that made it the most kinetically characterized enzyme, yet these studies focused on < 5% of its natural diversity. Here, we searched for fast‐carboxylating variants by systematically mining genomic and metagenomic data. Approximately 33, 000 unique rubisco sequences were identified and clustered into ≈ 1, 000 similarity groups. We then synthesized, purified, and biochemically tested the carboxylation rates of 143 representatives, spanning all clusters of form‐II and form‐II/III rubiscos. Most variants (> 100) were active in vitro, with the fastest having a turnover number of 22 ± 1 s −1 —sixfold faster than the median plant rubisco and nearly twofold faster than the fastest measured rubisco to date. Unlike rubiscos from plants and cyanobacteria, the fastest variants discovered here are homodimers and exhibit a much simpler folding and activation kinetics. Our pipeline can be utilized to explore the kinetic space of other enzymes of interest, allowing us to get a better view of the biosynthetic potential of the biosphere. Synopsis: The photosynthetic enzyme rubisco catalyzes the rate‐limiting step of carbon fixation in the Calvin‐Benson cycle. Here, analysis of previously uncharacterized natural form‐II and II/III rubiscos leads to identification of an enzyme with the fastest CO2 fixation rate described to date. Analysis of available metagenomic data allows identification and phylogenetic clustering of rubisco large subunit sequences. 143 form‐II and II/III rubisco variants were synthesized, purified, and biochemically tested for their maximal carboxylation rate. Form‐II rubisco from soil bacterium Gallionella sp. was found to have six‐fold faster carboxylation rate than the median plant enzyme, and nearly two‐fold faster than the fastest measured rubisco to date. Abstract : Metagenomic and biochemical analysis of previously uncharacterized naturally‐occurring form‐II and II/III rubiscos leads to identification of an enzyme with the fastest CO2 fixation rate described to date.